2020
DOI: 10.3390/economies8020049
|View full text |Cite
|
Sign up to set email alerts
|

Model Selection Procedures in Bounds Test of Cointegration: Theoretical Comparison and Empirical Evidence

Abstract: Only unstructured single-path model selection techniques, i.e., Information Criteria, are used by Bounds test of cointegration for model selection. The aim of this paper was twofold; one was to evaluate the performance of these five routinely used information criteria {Akaike Information Criterion (AIC), Akaike Information Criterion Corrected (AICC), Schwarz/Bayesian Information Criterion (SIC/BIC), Schwarz/Bayesian Information Criterion Corrected (SICC/BICC), and Hannan and Quinn Information Criterion (HQC)} … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Arandarenko and Vukojevic (2008) stated that formality and informality do not appear as binary choice, but rather along a spectrum of statuses, from full informality through semi-formality (tourism industry with sharing services, selfemployment, double payrolls in many small private firms), to full formality most typically in the public sector. The availability of secondary data can represent limitations for research (Badshah & Bulut, 2020;Dogru & Bulut, 2018;Guli c, 2018;Hall, 2002;Yalçinkaya et al, 2018). Finally, quality in tourism services cannot be measured merely by the number of stars, or by investment in infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Arandarenko and Vukojevic (2008) stated that formality and informality do not appear as binary choice, but rather along a spectrum of statuses, from full informality through semi-formality (tourism industry with sharing services, selfemployment, double payrolls in many small private firms), to full formality most typically in the public sector. The availability of secondary data can represent limitations for research (Badshah & Bulut, 2020;Dogru & Bulut, 2018;Guli c, 2018;Hall, 2002;Yalçinkaya et al, 2018). Finally, quality in tourism services cannot be measured merely by the number of stars, or by investment in infrastructure.…”
Section: Literature Reviewmentioning
confidence: 99%
“…which are included in cointegration analysis, ECM and VAR model; and variables are at most $ Ið2Þ: Therefore, the empirical part includes data sets from Equation ( 9) presented in four steps: first, summary statistics and visual inspection; second, Granger Causality test; third, ECM; and fourth, VAR and VECM following theoretical considerations (Brooks, 2019) and empirical approaches (Badshah & Bulut, 2020;Tang, 2010Tang, , 2012Tang, , 2014.…”
Section: Empirical Settingsmentioning
confidence: 99%
“…To check the robustness of the established models, we applied other lag criterion, such as the Schwarz Bayesian information criterion (SBC) and the Hannan-Quinn criterion (HQ), which applicability to testing the robustness of economic variables in developing countries has been demonstrated by many scholars, including by Aronu et al [97] in Nigeria, Aslam and Lebbe [98] in Sri Lanka, Iqbal Chaudhry et al [99] in China, Mehrara [100] in Iran, and Badshah and Bulut [101] in BRICS countries. We found that results had no change with the sign and significance of the coefficients.…”
Section: Robustness Checkmentioning
confidence: 99%
“…Daily price determination and diverse delivery options inherent in these markets lead to arbitrage opportunities. The increasing focus on sustainability in food supply chains, driven by various stakeholders, necessitates industry and retail assessment and enhancement of environmental and social performance [2]. Establishing sustainable supply chains is crucial for future competitiveness and stakeholder approval.…”
Section: Introductionmentioning
confidence: 99%